Institutional analysis of forest governance after the implementation of Law Number 23/2014 in North Sumatra Province, Indonesia - Affandi, Oding; Kartodihardjo, Hariadi; Nugroho, Bramasto; Ekawati, Sulistya (Forest and Society, 2021)
After the implementation of Law Number 23/2014 on Regional Government in Indonesia, the authority for forest management rests with the central and provincial governments. This study aims to (1) assess forest governance performance after the implementation of this law, (2) analyse the institutional aspects of forest governance after the implementation of this law and (3) formulate strategies to strengthen forest governance institutions. This study finds that although Law Number 23/2014 has been implemented in North Sumatra Province, the forestry sector remains centralistic; the characteristics of forest resources have not changed (these continue to be common pool resources) and the behaviour of the actors lacks synergy. In this scenario, the performance of forest governance has not improved significantly, as indicated by the incomplete designation of forest areas; the number of Kesatuan Pengelolaan Hutan that have not implemented the Badan Layanan Umum Daerah scheme; the low rights of access and low forest utilisation by the community; and the slow service process for permits; however, the costs for obtaining permits are according to regulations. This is in line with the results of this study’s institutional analysis, which show that (1) the provincial jurisdiction boundaries have narrowed, given that only the central government has authority over the forestry planning sub-function and forestry supervision; (2) many central government regulations continue to be used in forest management, characterising the low aspect of provincial regional representation rules; and (3) despite clear forest ownership rights, there are claims from other stakeholders, which indicates the low legitimacy of the parties. This study suggests that forest governance performance can be improved by expanding the jurisdiction boundaries through the assistance task mechanism to the provincial government; ensuring provincial government participation in formulating forest policies; and increasing the status of forest permit holders and managers from claimants to proprietors.